Peningkatan Perkembangan Motorik Halus Anak Usia 5-6 Tahun Melalui Kegiatan Kolase Bahan Alam : Studi Penelitian Tindakan Kelas - Ferranisa Vebriyanti; Lutfi Nur; Gilar Gandana (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to improve the fine motor skills of children aged 5–6 years through collage activities using natural materials. The method used is John Elliot's Classroom Action Research (CAR) model, which was carried out in two cycles. The research subjects were 10 children in Group B at the Kasih Bunda Early Childhood Education Center. Data collection techniques were conducted through observation and documentation. The results of the study indicate that collage activities using natural materials can significantly improve children's fine motor skills. The average percentage of fine motor skill development increased from 40% in the pre-cycle (Beginning to Develop category) to 68.33% in Cycle I (Developing as Expected) and reached 89.16% in Cycle II (Developing Very Well). Thus, natural material collage activities have proven to be an effective learning strategy for stimulating fine motor skills in young children in a fun and contextual way